Challenges in 11C charge breeding - Pitters, Johanna; Breitenfeldt, M.; Pahl, Hannes; Pikin, A.; Wenander, F. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2020)
In this paper we discuss the possibilities of using a charge breeding scheme based on an Electron Beam Ion Source for beam preparation of a radioactive 11C beam for hadron therapy. Test measurements under extreme operating conditions were conducted at the REX-ISOLDE facility to explore the limitations of the charge breeder for high-intensity, low-repetition-rate, molecular CO+ beams. Based on our findings, we discuss different possible scenarios of coupling a charge breeder with either a medical synchrotron or linear accelerator. This paper is a highly condensed version of an exhaustive report on the topic [1], which we would like to refer to for further details.
Available online: 23 May 2019
Die 11 im Titel ist hochgestellt
Gesehen am 20.04.2020